1993
DOI: 10.1111/j.1365-2109.1993.tb00637.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding attractants on the behaviour and performance of juvenile Penaeus monodon Fabricius

Abstract: Abstract. A study was conducted to obtain a measure of the potency of some potential and commercially used feeding attractants for Penaeus monodon Fabricius. Behavioural trials monitoring the feeding response of the shrimp were used to gauge the attractant qualities of the substances. A growth trial recording the feed intake, feed assimilation, growth, food conversion and survival rates of the shrimp was used to assess further the feeding stimulant properties of the substances. Replicate groups of juvenile sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 20 publications
1
16
0
1
Order By: Relevance
“…(1985) and Pittet et al. (1996) with penaeid shrimp and by Costa‐Pierce & Laws (1985) with the fresh water prawn Macrobrachium rosenbergii whereas no effect was observed by Hartati & Briggs (1993) with penaeids. More recently, Smith et al.…”
Section: Discussionmentioning
confidence: 96%
“…(1985) and Pittet et al. (1996) with penaeid shrimp and by Costa‐Pierce & Laws (1985) with the fresh water prawn Macrobrachium rosenbergii whereas no effect was observed by Hartati & Briggs (1993) with penaeids. More recently, Smith et al.…”
Section: Discussionmentioning
confidence: 96%
“…As such, compounds that can enhance feeding behaviour have received a lot of attention as a potential refinement in crustacean aquaculture (e.g. Hartati & Briggs ; Smith et al . ; Nunes et al .…”
Section: How Can We Use Behaviour To Improve Shrimp Aquaculture?mentioning
confidence: 99%
“…Despite the significant body of research into feeding effectors for crustaceans, few researchers have quantified the effect feeding effectors have on feed intake of penaeid shrimp (Lee & Meyers 1997). Hartati & Briggs (1993) observed that the addition of feeding effectors did not increase the feed intake during a growth trial. However, as they used only two replicates for each treatment, their findings must be interpreted with caution.…”
Section: Growth Response Experimentsmentioning
confidence: 99%
“…However in their study, the estimates of feed intake appear to be excessive with reported feed conversion ratios (FCRs) of between 4.4 and 12. Hartati & Briggs (1993) assessed the feed intake and growth response of P. monodon fed a casein‐based, semi‐purified feed that was supplemented with a range of potential and commercial feeding effectors. None of the substances tested resulted in a significant increase in feed intake or assimilation.…”
Section: Introductionmentioning
confidence: 99%